Pemanfaatan Instrumen Tes dan Nontes Pada Layanan Konseling - Ade Chita Putri; Azura Mahyuliza Sembiring; Hilda Amaliyah Lubis; Irma Suryani Nasution; Lenni Dalimunthe (Jurnal Administrasi Pendidikan dan Konseling Pendidikan, 2022)
The study aims to reveal how spirit guides or counselors can utilize school instruments both in tests and nontests. From data collected information that when offering counseling teacher services only enables the instrument of test by giving a few issues to know its cognitive levels but not with its affective and psychological qualities or so-called nontest instruments. The study USES a qualitative method, the data used for the study USES computer suggestinaire (online/ online) angket from research data that many school guidance teachers or counselors have not been able to get the test and test non-test instruments in the country. The mamsort of research so that the guidance teacher or counselor can evaluate themselves and to get more insight into the unknown about the test and non-test instruments.